MRI‐guided needle localization: Indications, tips, tricks, and review of the literature. Issue 3 (28th March 2019) - Raj, Sean D.; Agrons, Michelle M.; Woodtichartpreecha, Piyanoot; Kalambo, Megan J.; Dogan, Basak E.; Le‐Petross, Huong; Whitman, Gary J.
Abstract: We describe the history of, indications for, and techniques involved in MRI‐guided needle localization (MRI‐NL). MRI‐NL continues to be a safe, effective method of sampling lesions that are only detected with MRI, particularly for anatomically challenging lesions such as those near the chest wall, the nipple, the skin, and/or in close proximity to implants.